Is there any association of apolipoprotein E gene polymorphisms with metabolic syndrome in a young population of Croatian origin? - Ivana Karmelić; Jasna Lovrić; Tamara Božina; Ana Merkler; Nada Božina; Jadranka Sertić (Taylor & Francis Group, 2017)
Background: Apolipoprotein E has an important role in lipid metabolism and adipocyte activity and apo E gene (APOE) might serve as a potential determinant of metabolic syndrome (MetS). Aim: The aim of the presented study was to investigate the association between APOE polymorphism and MetS in young adult subjects of Croatian origin. Methods: This study measured biochemical and anthropometric parameters of 149 young (aged 20-33) subjects. The APOE was genotyped by real-time PCR. Results: No APOE genotype significantly increased the risk for development of MetS. Significant association was found between APOE polymorphism and elevated blood pressure (EBP) (p = .019). The carriers of the ɛ4 allele had decreased risk for EBP (OR = 0.28, 95% CI) compared to ɛ3 allele carriers (ɛ3 allele vs others, χ2 = 7.08; p = .005). APOE alleles were significantly associated with the concentration of TC and LDL-C (χ2 = 12.11, p = .002 and χ2 = 15.76, p < .001, respectively). With diet as a modification covariate there was a significant correlation of APOE alleles with the concentrations of adiponectin and leptin (χ2 = 7.076; p = .029 and χ2 = 7.46; p = .024, respectively). Conclusion: Although APOE variants were not confirmed as the risk factor for development of MetS, the APOE alleles were associated with some of the metabolic parameters in young Croatian subjects. The relation of APOE alleles with a concentration of adiponectin and leptin depends on the diet intake.